Stabilin Receptors: Role as Phosphatidylserine Receptors - Seung-Yoon Park; In-San Kim (Biomolecules, 2019)
Phosphatidylserine is a membrane phospholipid that is localized to the inner leaflet of the plasma membrane. Phosphatidylserine externalization to the outer leaflet of the plasma membrane is an important signal for various physiological processes, including apoptosis, platelet activation, cell fusion, lymphocyte activation, and regenerative axonal fusion. Stabilin-1 and stabilin-2 are membrane receptors that recognize phosphatidylserine on the cell surface. Here, we discuss the functions of Stabilin-1 and stabilin-2 as phosphatidylserine receptors in apoptotic cell clearance (efferocytosis) and cell fusion, and their ligand-recognition and signaling pathways.